The Role of the Civil Service Police Unit in Public Order and Community Peace - Sugiyanto; Choiriyah, Ilmi Usrotin (Indonesian Journal of Cultural and Community Development, 2025)
The general background maintenance of public order and community peace is a critical aspect of local governance, particularly in urban settings where diverse populations coexist. Specific background reveals that the Civil Service Police Unit (Satpol PP) plays a significant role in upholding these values, yet there is limited research examining their effectiveness in specific districts. Knowledge gap persists in understanding the comprehensive functions and impacts of Satpol PP in maintaining public order within local communities. This study aims to analyze and describe the role of the Satpol PP in implementing public order and community peace in a specific district. Results indicate that the Satpol PP engages in various activities, including community outreach, training for local volunteers, and proactive measures to prevent disturbances, demonstrating a multi-faceted approach to their responsibilities. Novelty lies in the identification of active, participatory, and passive roles that the Satpol PP adopts, which offers a more nuanced understanding of their functions. Implications of this research suggest that strengthening the capacity of the Satpol PP could enhance community engagement and further improve public safety. By providing a detailed examination of their roles, this study contributes to the broader discourse on local governance and community development, offering insights that may inform policy and practice in similar contexts. Highlights: Active role in maintaining public order through various strategies. Community participation in reporting issues to the Satpol PP. Training programs to enhance the capabilities of Linmas and Satpol PP personnel. Keywords: Satpol, Community, Public Order, Participation, Capacity Building